Distinguishing Physical and Biological Controls on the Carbon Dynamics in a High‐Arctic Outlet Strait. Issue 3 (2nd March 2023) - Burgers, T. M.; Miller, L. A.; Rysgaard, S.; Mortensen, J.; Else, B.; Tremblay, J.‐É.; Papakyriakou, T.
Abstract: The water mass assembly of Nares Strait is variable, owing to fluctuating wind forcings over the central Arctic Basin, and irregular northward flows from the West Greenland Current (WGC) in Baffin Bay. Here we characterize the physico‐chemical properties of the water masses entering Nares Strait in August 2014. We employ an extended optimum multi‐parameter (OMP) analysis to estimate the mixing fractions of predefined source water masses, and to distinguish the role of physical and biological processes in governing the distribution of dissolved inorganic carbon (DIC) in Nares Strait. We show the first documented evidence of Siberian shelf waters arriving in Nares Strait, along with a diluted upper halocline layer of partial Pacific‐origin. These mixed‐origin water masses appear to play an important role in driving a modest phytoplankton bloom in Kane Basin, leading to decreased surface p CO2 concentrations in Nares Strait. Although inorganic nitrogen was already limited near the surface in northern Nares Strait, the rather shallow upper halocline layer and the shoaling bathymetry in Kane Basin facilitated upwelling of nutrients to the surface. Our observations suggest that the positioning of the Transpolar Drift, and hence the balance of Atlantic and Pacific water delivered to Nares Strait, may play an important role in regional biological productivity and carbon uptake from the atmosphere. We also observed water masses from the WGC transported as far north as Kane Basin, contributing to relatively high p CO2 and low pH in the intermediate and deep water column of southern Nares Strait and northern Baffin Bay. Plain Language Summary: Nares Strait is the northernmost outflow channel from the Arctic Ocean, located between Ellesmere Island and northern Greenland. The physical and chemical properties of the waters exiting the Arctic Ocean through Nares Strait play an important role in freshwater transport, carbon dynamics, and in supplying nutrients to marine ecosystems downstream, including delivery to the historically productive North Water polynya region, and eventually the North Atlantic. The water masses transported through Nares Strait are known to change depending on the predominant wind patterns over the Arctic Ocean. Here we document the export of surface waters that originated from the Siberian shelf seas, on the other side of the Arctic Ocean, carrying with them a strong river water signal. This study demonstrates that the carbon dynamics in Nares Strait are largely dictated by mixing of water masses from the north and south, with local biology playing an important role in facilitating atmospheric CO2 drawdown in Nares Strait and further downstream. Key Points: Siberian shelf waters are identifiable in Nares Strait, in the high Canadian Arctic Archipelago The position of the Transpolar Drift determines surface water properties in Nares Strait, affecting regional productivity and CO2 uptake Primary production is limited in Nares Strait due to nutrient‐limited surface waters, but plays an important role in lowering surface p CO2